Development of statistically unbiased 21st century hydrology scenarios over La Plata Basin - Saurral, Ramiro Ignacio (2013)
There is an increasing demand for future climate scenarios, particularly for impact studies. In this study, simulation outputs taken from a set of three Regional Climate Models (RCMs) are used to force a hydrologic model to derive future streamflow scenarios for La Plata Basin (LPB). As RCMs have biases in their mean precipitation and temperature fields, a statistical scheme is previously used to remove the systematic part of the bias. Future hydrologic scenarios were derived considering two future periods: 2021-2040 (near future) and 2071-2090 (far future). In terms of climate projections, RCMs predict warmer conditions in almost the whole basin, while precipitation variations are not uniform in sign across the region but overall tend to be positive over the southern part of the basin. Nevertheless, a trend towards a gradual increase in streamflow was found for the majority of the rivers in the basin particularly for the near future followed by less uniform variations towards the end of the present century. Future changes in the largest monthly streamflow are similar to those in the mean values, with also some differences among RCMs and on the period and sub-basin considered.